La periferia y la vivienda popular... ¿Factores de crecimiento, bienestar y/o desarrollo?. (2021)
This text tries to contribute to the discussion around the expanding of the cities specially when they make it on the urban peripheries with popular dwellings and a great impact on the environment and the urban economy. The author hopes that this article promotes the searching of new possibilities for the planning process in the city of Pereira, mainly through our own research and work.